Postoperative blood salvage versus allogeneic blood transfusion in total knee and hip arthroplasty: a literature review - Leigheb, Massimiliano; Pogliacomi, Francesco; Bosetti, Michela; Boccafoschi, Francesca; Sabbatini, Maurizio; Cannas, Mario; Grassi, Federico (Acta Biomedica Atenei Parmensis, 2016)
Background and aim of the work: We aimed to compare Postoperative Blood Salvage (PBS) with Allogeneic Blood Transfusion (ABT) in patients undergoing Total Hip and Knee Arthroplasty (THA, TKA).  Methods: A bibliographic research was carried out in order to review the literature dedicated to postoperative blood salvage in major orthopaedic surgery, excluding papers dealing exclusively with preoperative autologous donation, intraoperative blood salvage and ABT. PBS and ABT were compared according to complications, costs and duration of hospitalization. PBS effectiveness in reducing ABT was also assessed. Results: PBS system is useful for reducing the complication rate and the length of hospital stay if compared to ABT. Costs for the reinfusion of unwashed shed blood, washed blood, and allogeneic transfusion are controversial among the different authors. Several papers demonstrate that PBS significantly reduces the need of postoperative ABT in both THA and TKA, while there is low evidence that PBS does not affect the risk of surgical wound complications. To reduce potential risks related to PBS, including non-hemolytic febrile reaction, the reinfusion of saved blood should begin within 4-6 hours after the start of collection through the wound drainage. Conclusions: According to literature, PBS appears to be a valid alternative to ABT, which is the standard treatment for postoperative anemia in THA and TKA. Contraindications to PBS must be ruled out before recommending it to patients undergoing major orthopaedic procedures.